A result on the acoustic characteristics of the Mixture of Counter-phase Counteract and Split-gas Rushing muffler - Shao Ying-li (MATEC Web of Conferences, 2016)
The exhaust noise, which falls into low-frequency noise, is the dominant noise source of a diesel engines and tractors. The traditional exhaust silencers, which are normally constructed by combination of expansion chamber, and perforated pipe or perforated board, are with high exhaust resistance, but poor noise reduction especially for the low-frequency band noise. For this reason, a new theory of exhaust muffler of diesel engine based on counter-phase counteracts has been proposed. The mathematical model and the corresponding experimental validation for the new exhaust muffler based on this theory were performed.